2017
DOI: 10.1111/bjh.15042
|View full text |Cite
|
Sign up to set email alerts
|

Nilotinib after imatinib first‐line: a real‐life longitudinal cohort of patients with chronic myeloid leukaemia in chronic phase

Abstract: This prospective, observational study enrolled 150 adult patients with chronic myeloid leukaemia (CML) in chronic phase (CP) treated with nilotinib as second-line after imatinib, in a real life setting in France. Two-thirds of patients switched to nilotinib treatment due to lack of imatinib efficacy. Of 146 evaluable patients, 16 (11·0%) (95% confidence interval: 6·4-17·2%) achieved uMR , defined as undetectable molecular disease in cDNA with MR sensitivity (≥10 000 ABL1 transcripts) at 18 months and confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Only approximately 14% of the patients changed TKI in their first year of treatment but there were discontinuations in 23% of the cases and almost 52% of interruptions. These results are consistent with studies that investigate treatment patterns with protein kinase inhibitors among patients with CML (35)(36)(37)(38). Reasons for switching or discontinuation could be adverse effects or intolerance to TKI (38,39).…”
Section: Patterns Of Tki Treatment and Healthcare Resources Consumptionsupporting
confidence: 88%
“…Only approximately 14% of the patients changed TKI in their first year of treatment but there were discontinuations in 23% of the cases and almost 52% of interruptions. These results are consistent with studies that investigate treatment patterns with protein kinase inhibitors among patients with CML (35)(36)(37)(38). Reasons for switching or discontinuation could be adverse effects or intolerance to TKI (38,39).…”
Section: Patterns Of Tki Treatment and Healthcare Resources Consumptionsupporting
confidence: 88%
“…Nilotinib is more potent and selective ATPcompetitive inhibitor of BCR/ABL1 tyrosine kinase than imatinib and it is more active against imatinib-resistant mutant forms of enzyme [16,17]. Multicenter trials and a real-life longitudinal proved nilotinib efficacy in the CML patients with imatinib failure [8,18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that nilotinib (the second generation TKI) is effective in patients with CML after imatinib failure [7,8]. But the influence of nilotinib on leukemic clones with additional chromosomal abnormalities has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…The 7-year update of the phase 3, dose-optimization study of dasatinib in 670 CML-CP patients resistant or intolerant to imatinib confirmed that 100 mg daily is the best dose, with PFS and OS of 42% and 65% respectively, a major molecular response (MMR) rate of 46% and an acceptable safety profile, with drug-related pleural effusion rate of 28% and < 5% of pulmonary hypertension and arterial ischemic events [ 8 ]. With a shorter follow-up, nilotinib has shown similar results both in a phase 2 study (CCyR rate at 48 months of 45%, estimated PFS and OS at 48 months 57% and 78%, respectively) [ 9 ], and in a French real-life experience (66% patients achieved MMR and 44% achieved a deep molecular response (DMR) after a median time of nilotinib therapy around 6 months; survival not reported but only 1/146 patients progressed to advanced phase) [ 10 ]. More recently, an Italian group retrospectively analyzed 163 patients treated with 2GTKI (dasatinib, n = 95 or nilotinib, n = 68) after imatinib failure, reporting rates of CCyR (75%), MMR (60%) and DMR (37%) higher than previous studies, 5-year PFS and OS around 85%, good persistence of treatment (60% at 4 years) and comparable efficacy and safety of the two TKIs [ 11 ].…”
Section: Imatinib As First-line Therapymentioning
confidence: 93%